Estimación de la huella de carbono en ganadería lechera mediante el software Cool Farm Tool (CFT) en la provincia de Carchi – Ecuador. - Vásquez Merlo, Melany Paulina (2022)
Greenhouse Gas (GHG) emissions can be caused by many factors, including dairy farming. The accumulation of these gases in the atmosphere generates an increase in temperature, known as global warming. Few investigations have been carried out about the emissions generated by this area in Ecuador, that´s the reason why this investigation proposed to calculate the emissions generated by dairy farms in the province of Carchi - Ecuador, as a first approach to producers and recommend farm management practices. The objective of this research was to estimate the amount of GHG generated by dairy farming in this area, and with this propose practices to reduce emissions. A characterization of the milk production of 170 dairy cattle farms in the study area was carried out, through surveys that collected socioeconomic information (age of the producer, studies carried out, level of education, years of experience dedicated to dairy farming)\; livestock and pasture management (area dedicated to dairy farming, number of liters/year, amount of energy used per owner, fertilization). An association was made between socioeconomic variables and management of productive systems. According to the characteristics of the cattle, they were grouped into three categories: small farms (1-9 cows), medium-sized (10-30 cows) and large (greater than 31 cows). Subsequently, the total emissions generated were estimated, per hectare, per liter of milk production and by type of emissions for each group, using the Cool Farm Tool software. The study identified, in the context of GHG mitigation actions, several practices that can help generate livestock farming that is more aware of the emissions that this practice causes to the environment.